2020
DOI: 10.1002/cyto.b.21943
|View full text |Cite
|
Sign up to set email alerts
|

Utility of CD36 as a novel addition to the immunophenotypic signature of RAM‐phenotype acute myeloid leukemia and study of its clinicopathological characteristics

Abstract: Introduction: In 2016, Children Oncology Group (COG) described a new high-risk subtype of acute myeloid leukemia (AML) with a distinct immunophenotypicsignature, RAM-phenotype (RAM-AML). Data on clinical and laboratory features of RAM-AML are still limited to COG report only. Herein, we report the clinicopathological characteristics and detailed immunophenotypic features of RAM-AML patients. In COG report, 38% of RAM-AML belonged to acute megakaryoblastic leukemia (AMKL)-subtype. Hence, we further compared the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 25 publications
(44 reference statements)
6
19
2
Order By: Relevance
“…CD36 is expressed in many cell types, which mediates immune recognition, in ammation, molecular adhesion, apoptosis and lipid uptake as a scavenger receptor [25][26][27].It has been demonstrated that CD36 could regulate the proliferation, metastasis, and angiogenesis of different tumor types, such as Esophageal squamous cell carcinoma [28], gastric cancer [29], and leukemia [30]. The role of CD36 in HCC is usually related to the tumor microenvironment, and the procedure is to participate in the progression of HCC mediated by tumor metabolic reprogramming [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…CD36 is expressed in many cell types, which mediates immune recognition, in ammation, molecular adhesion, apoptosis and lipid uptake as a scavenger receptor [25][26][27].It has been demonstrated that CD36 could regulate the proliferation, metastasis, and angiogenesis of different tumor types, such as Esophageal squamous cell carcinoma [28], gastric cancer [29], and leukemia [30]. The role of CD36 in HCC is usually related to the tumor microenvironment, and the procedure is to participate in the progression of HCC mediated by tumor metabolic reprogramming [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by a unique immunophenotype of bright expression of CD56, dim to negative CD45, dim to negative CD38, and the absence of HLA‐DR 1 . There is a high frequency of acute megakaryoblastic leukemia (AMKL) among the RAM phenotype 1,2,5,9,10 . A high prevalence of more than 60% of the CBFA2T3‐GLIS2 fusion gene, which may act as pathogenic driver in this group of patients, is also reported in the literature 1,2,5,10–15 .…”
Section: Introductionmentioning
confidence: 89%
“…There is a high frequency of acute megakaryoblastic leukemia (AMKL) among the RAM phenotype 1,2,5,9,10 . A high prevalence of more than 60% of the CBFA2T3‐GLIS2 fusion gene, which may act as pathogenic driver in this group of patients, is also reported in the literature 1,2,5,10–15 . This phenotype is associated with a significantly worse outcome with a high induction failure rate and poor event free and overall survival 1,2,5,10,11 .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This subtype of AML was immunophenotypically characterized with bright CD56, reduced expression of CD45 and CD38 and the absence of HLA‐DR expression. In this issue Panda et al, 2021 report on studying 1102 patients with a median age of 2 years, of which 11 were RAM‐AML patients. Additionally, CD36 expression was found to be consistently absent from the immunophenotypic signature.…”
mentioning
confidence: 99%